Discharge phenomena associated with a preheated wire explosion in vacuum: Theory and comparison with experiment - Beilis I. I.; Baksht B. B.; Oreshkin V. I.; Russkikh A. G.; Chaikovskii S. A.; Labetskii A. Yu.; Ratakhin N. A. Nikolay Aleksandrovich; Shishlov A. V. Aleksandr Viktorovich (2007, 2007)
Title screen